Molecular dynamics study of the swelling and osmotic properties of compact nanogel particles. Issue 33 (15th August 2022) - Chremos, Alexandros; Douglas, Jack F.; Basser, Peter J.; Horkay, Ferenc
Abstract : Molecular architecture of nanogel particle. Abstract : Owing to their great importance in materials science and other fields, we investigate the solution and osmotic properties of uncharged compact nanogel particles over a wide range of solvent quality and particle concentration by molecular dynamics (MD) simulations. We characterize the osmotic pressure by estimating the second and third virial coefficients, and by extension, we identify the θ -point where the second virial coefficient vanishes. Calculations of the structure factor indicate that these particles are similar to macrogels in that the particle-like scattering profile disappears at moderate concentrations. We also find that improving the solvent quality enhances the spatial segmental uniformity, while significant heterogeneous structure arises near the θ -point. Well below the θ -point where the second osmotic virial coefficient vanishes, these heterogeneous structures become less prevalent as the particles tend to collapse. We also investigate the degree of swelling and structure of compact nanogel particles with a variable excluded volume interaction and gel particle concentration. The osmotic modulus and the scaling exponents in good and θ -point conditions of these gels are characteristic of interacting randomly branched polymers, i.e., "lattice animals".